2015
DOI: 10.1099/jgv.0.000221
|View full text |Cite
|
Sign up to set email alerts
|

HCV upregulates Bim through the ROS/JNK signalling pathway, leading to Bax-mediated apoptosis

Abstract: We previously reported that hepatitis C virus (HCV) infection induces Bax-triggered, mitochondrion-mediated apoptosis by using the HCV J6/JFH1 strain and Huh-7.5 cells. However, it was still unclear how HCV-induced Bax activation. In this study, we showed that the HCV-induced activation and mitochondrial accumulation of Bax were significantly attenuated by treatment with a general antioxidant, N-acetyl cysteine (NAC), or a specific c-Jun N-terminal kinase (JNK) inhibitor, SP600125, with the result suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 56 publications
(71 reference statements)
1
12
1
1
Order By: Relevance
“…The ROS/JNK signaling pathway has been shown to upregulate Bim and lead to Bax-mediated apoptosis. 28 Indeed, NAC reduced ROS production (Figure 8b) and Bim expression (Figure 8g), supporting the hypothesis that the ROS-Bim pathway is one of the major cause of apoptosis in Tsc1-deficient DCs. Taken together, Tsc1 promotes DC survival via the independently repression of the mTORC1 and ROS-Bim pathways.…”
Section: Resultssupporting
confidence: 77%
“…The ROS/JNK signaling pathway has been shown to upregulate Bim and lead to Bax-mediated apoptosis. 28 Indeed, NAC reduced ROS production (Figure 8b) and Bim expression (Figure 8g), supporting the hypothesis that the ROS-Bim pathway is one of the major cause of apoptosis in Tsc1-deficient DCs. Taken together, Tsc1 promotes DC survival via the independently repression of the mTORC1 and ROS-Bim pathways.…”
Section: Resultssupporting
confidence: 77%
“…This should be further examined in future experiments. Interestingly, recent observations have shown that infection with HCV-2a alone may induce activation of JNK/Bim and apoptosis in Huh-7.5 cells, although we did not observe increased JNK or Bim activation in OR6 cells without palmitate treatment [ 28 ]. Likewise, in our study, constitutive apoptosis was not elevated in OR6 cells compared to cured cells.…”
Section: Discussioncontrasting
confidence: 88%
“…Although prior studies showed sustained activation of JNK in HCV-infected cells, it was unclear how JNK would play a role in lipoapoptosis in this condition [ 28 ]. Here, palmitate treatment triggered phosphorylation of JNK and activation of Bim.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS/JNK signalling has been reported to be important for Bax-mitochondrial apoptotic pathway 43,44 . Thus, we investigate whether Bax is involved in lobaplatin-induced pyroptosis via ROS/JNK signalling.…”
Section: Resultsmentioning
confidence: 99%